Energy Company Stock Performance: What is the role of Leverage, Dividend Payout Ratio, and EVA? - Khotimah , Rerita Khusnul; Cahyaningsih, Diyah Sukanti; Listyowati; Sri Werdiningsih (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study examines the impact of the Debt-to-Equity Ratio (DER), Dividend Payout Ratio (DPR), and Economic Value Added (EVA) on stock returns in oil, gas, and coal subsector companies listed on the Indonesia Stock Exchange for the period from 2020 to 2023. The analytical methods used include classical hypothesis testing, multiple linear regression, and other methods. Based on the research results, the Debt-to-Equity Ratio and Dividend Payout Ratio were shown to have no significant effect on stock returns. The significance values for DER and DPR were 0.292 and 0.568, respectively. This finding indicates that a company’s funding structure (leverage) and dividend policy are not primary factors investors consider when making investment decisions in this sector. Conversely, Economic Value Added (EVA) had a significant and positive effect on stock returns, with a significance value of 0.001. This demonstrates that a company’s ability to create economic value added is a key indicator that investors take seriously when assessing company performance and making investment decisions. For further research, it is recommended to explore other potential variables, including both internal factors such as profitability and liquidity, as well as external factors such as macroeconomic conditions and commodity prices, to provide a more comprehensive understanding of the determinants of stock returns